ASSESSMENT OF MEASUREMENT UNCERTAINTY IN CALIBRATION OF MEASURING INSTRUMENTS USED IN INFORMATION-MEASUREMENT SYSTEMS - Rakhmanova G. S.; Agzamova M. R. (Journals Park Publishing, 2024)
Classification of measuring instruments is given in article used for calibration, an assessment of uncertainty of measurements, calibration by a method of a direct assessment, in particular, carrying out an assessment with use of basic algorithm developed on the documents GUM, VRACHEM and EA -4/02.
Keywords: Assessment, classification, ISOMEC standard, calibration, method, measurement.